(untitled) - Robert N Brady (Englewood Cliffs, New Jersey, 1996)
The book reflects both traditional and state-of-the-art technology, covering basic theory, operation of systems, and modern applications.Due to the industry-wide adoptation of electronic fuel injection systems and the general movement toward electronic control of all major system, This book emphasizes the operation, diagnosis, and troubleshooting of these technically advanced engine systems. The book also includes hundreds of clear, detailed illustrations; a coverage of engines from all major manufacturers; a comprehensive coverage of all engines systems, including the very latest in electronic controls; emphasis on the basic principles common to all diesel engines; systematic approach to diagnostic and servicing procedures
Keywords: diesel motor - fuel system